Characteristics and community stabilities of the resource islands formed by Salix paraplesia shrubs in the mobile sandy land of the upper reaches of the Yellow River in Sichuan Province - Li He; Miaomiao Su; Dechao Chen; Houyuan Zeng; Xuemei Huang; Honglin Li; Shilei Wu; Hang Song; Xue Jiang; Kejun Wu; Jingyu Yang; Wuxian Yan; et al. (Heliyon)
This study comprehensively analyzes the physical and chemical properties of soil across different layers under Salix paraplesia shrubs, comparing these properties inside and outside the shrub canopies. It also examines species diversity and community stability in these areas, discussing the impact of soil from resource islands at different formation stages on vegetation restoration. Focusing on Salix paraplesia shrubs over varying restoration periods (45 years, 25 years, and 13 years), with unrepaired mobile sandy land serving as the control, the results are as follows: (1) As vegetation restoration progresses, the content of soil organic matter (SOM) and alkali-hydrolyzable nitrogen (AN) significantly increase. After 45 years of restoration, SOM and AN contents are 250.08 % and 442.43 % higher than in the control. SOM, AN, and total phosphorus (TP) contents are greater under the shrubs than outside the canopies, indicating pronounced fertilizer accumulation. (2) The number of plant species increases during the restoration process, with 18 more species present after 45 years compared to the control. Community diversity is highest after 13 years of restoration, with greater overall diversity outside the canopies than under the shrubs. These differences decrease as restoration progresses. (3) The stability of Salix paraplesia shrub communities is higher outside the canopies compared to under the shrubs. As restoration proceeds, stability differences between these areas diminish. The Euclidean distances for community stability outside and under the canopies are 13.97 and 14.68, respectively, after 45 years, indicating relative stability. (4) In the early stages of restoration, soil carbon (C) and nitrogen (N) significantly impact species diversity, while in the later stages, phosphorus (P) content becomes more limiting. Resource islands enhance plant community stability and vegetation restoration, playing a crucial role in ecological protection and vegetation restoration in the alpine sandy land of the Yellow River's upper reaches.